Rural community birth: Maternal and neonatal outcomes for planned community births among rural women in the United States, 2004‐2009. Issue 2 (13th November 2017) - Nethery, Elizabeth; Gordon, Wendy; Bovbjerg, Marit L.; Cheyney, Melissa
Abstract: Background: Approximately 22% of women in the United States live in rural areas with limited access to obstetric care. Despite declines in hospital‐based obstetric services in many rural communities, midwifery care at home and in free standing birth centers is available in many rural communities. This study examines maternal and neonatal outcomes among planned home and birth center births attended by midwives, comparing outcomes for rural and nonrural women. Methods: Using the Midwives Alliance of North America Statistics Project 2.0 dataset of 18 723 low‐risk, planned home, and birth center births, rural women (n = 3737) were compared to nonrural women. Maternal outcomes included mode of delivery (cesarean and instrumental delivery), blood transfusions, severe events, perineal lacerations, or transfer to hospital and a composite (any of the above). The primary neonatal outcome was a composite of early neonatal intensive care unit or hospital admissions (longer than 1 day), and intrapartum or neonatal deaths. Analysis involved multivariable logistic regression, controlling for sociodemographics, antepartum, and intrapartum risk factors. Results: Rural women had different risk profiles relative to nonrural women and reduced risk of adverse maternal and neonatal outcomes in bivariable analyses. However, after adjusting for risk factors and confounders, there were no significant differences for a composite of maternal (adjusted odds ratio [aOR] 1.05 [95% confidence interval CI 0.93‐1.19]) or neonatal (aOR 1.13 [95% CI 0.87‐1.46]) outcomes between rural and nonrural pregnancies. Conclusion: Among this sample of low‐risk women who planned midwife‐led community births, no increased risk was detected by rural vs nonrural status.